Labour force participation elasticities and the move away from a flat tax: The case of Slovakia - Matus Senaj; Zuzana Siebertova; Norbert Svarda; Jana Valachyova (IZA Journal of European Labor Studies, 2016)
This paper provides a microeconometric analysis of labour force participation elasticities in Slovakia where we study the elasticity with respect to a unique tax reform whereby the flat tax was backtracked and replaced by a progressive tax. By estimating a probability model for labour force participation, we show that the low-skilled and females are groups that are particularly responsive to changes in income taxes and transfers. We perform a microsimulation analysis of two scenarios of flat-tax regime abolishment. We find that the recent departure from the flat-tax system in Slovakia in 2013, which introduced two tax brackets in personal income taxation, only negligibly reduced the average probability of being economically active at the extensive margin. A more significant average effect has been found in a hypothetical scenario with a similar fiscal revenue impact, simulating a departure from the flat-tax system by reintroducing five tax brackets. We show the different impacts of the two distinct scenarios of abolishing the flat tax on selected subgroups of the population.
Keywords: H31; H53; I38; J21; 330; Labour force participation elasticity; Extensive margin; Microsimulation; Flat tax